2011
DOI: 10.1002/prot.23021
|View full text |Cite
|
Sign up to set email alerts
|

Progress in the structural prediction of G protein‐coupled receptors: D3 receptor in complex with eticlopride

Abstract: Predicting the three-dimensional structure of ligand-receptor complexes involving G protein-coupled receptors (GPCRs) is still a challenging task in rational drug design. To evaluate the reliability of the GPCR structural prediction, only a couple of community-wide assessments have been carried out. Our participation in the last edition, DOCK2010, involved the blind prediction of the dopaminergic D(3) receptor in complex with the D(2)/D(3) selective antagonist eticlopride for which the crystal structure has be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
24
0

Year Published

2012
2012
2015
2015

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(26 citation statements)
references
References 23 publications
2
24
0
Order By: Relevance
“…It has been shown, however, that standard MD may improve docking poses of various targets [30] including GPCRs [33,34]. Similar to our study, Orbiol-Pardo et al [32] showed that MD substantially affects the conformation of ECL2 and improves docking of ecticlopride to the D 3 receptor. In most cases, our study demonstrated that simulation of hundreds of nanoseconds of conventional MD eliminates differences between the top pose and crystal structure in interacting with the receptor.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…It has been shown, however, that standard MD may improve docking poses of various targets [30] including GPCRs [33,34]. Similar to our study, Orbiol-Pardo et al [32] showed that MD substantially affects the conformation of ECL2 and improves docking of ecticlopride to the D 3 receptor. In most cases, our study demonstrated that simulation of hundreds of nanoseconds of conventional MD eliminates differences between the top pose and crystal structure in interacting with the receptor.…”
Section: Discussionsupporting
confidence: 90%
“…Analysis of ligand-receptor interactions shows that, in agreement with previous findings [32,48], modeling of ligand interactions with ECL2 was most problematic (Fig. 2, Table 6 and Supplementary Information Text File S1).…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…Both compounds, the natural ligand serotonin (used as a control for balanced agonism) and 2C-N, were docked into a fully activated model of the serotonin 5-HT 2A receptor. Notably, the modeling approach used to obtain these ligand-receptor complexes, which is detailed in the Materials and Methods section, has previously proven to be highly effective in predicting highresolution ligand-receptor complexes for related targets (Obiol-Pardo et al, 2011). The resulting complexes were embedded into a hydrated lipid bilayer, ionized to a physiologic concentration and subjected to extensive molecular dynamic simulations.…”
Section: Resultsmentioning
confidence: 99%
“…Then, models for dopamine D(2), D(3), and D(4), serotonin 5-HT(1B), 5-HT(2A), 5-HT(2B), and 5-HT(2C), histamine H(1), and muscarinic M(1) receptors were generated using as template the structure of the β₂-adrenergic receptor [70] and assessed in high-throughput docking campaigns [71]. This strategy was also applied in the blind prediction of the D(3) receptor structure complexed with the D(2)/D(3) selective antagonist eticlopride (GPCR DOCK 2010 challenge [44]), where a successful prediction was achieved in one out of three submitted models [72]. A detailed description of the modeling of 5-hydroxytryptamine receptors 1B and 2B in GPCR DOCK 2013 can be found elsewhere [53].…”
Section: Integral Binding-site Modeling and Refinementmentioning
confidence: 99%